(untitled) (Sirte University Journal of Humanities, 2025)
The study aims to identify one of the natural hazards to which the study area is exposed due to its astronomical and geographical location .drought is one of the most complex environmental problems and its effects are reflected on various elements and systems of the natural environment. due to the fragility of the ecosystem in the Bani Waleed region, drought has significantly affected soil, vegetation and rain-fed agriculture, which contributed significantly to the creation of other environmental problems, the most important of which are dust storms, which had a negative impact on the natural and human environment in the region, through their impact on human health and most prominent activities such as agriculture and transportation.